Transformasi Regulasi Dan Kebijakan Hukum Pidana Dalam Ekosistem Bisnis Digital Di Indonesia - Asneliwarni; Aris Irawan; Fitri Wahyuni (Indragiri Law Review, 2025)
The reconstruction of criminal provisions that correspond to the characteristics of electronic transactions and legal relationships in digital spaces has become increasingly urgent within Indonesia’s evolving digital economy. Regulatory dynamics demonstrate normative fragmentation, overlapping statutory frameworks, and unclear boundaries of criminal liability among legal subjects, particularly business actors, digital platform providers, and users. Such conditions generate legal uncertainty and create the risk of overcriminalization in digital business practices. This article aims to analyze the transformation of regulatory frameworks and criminal provisions within Indonesia’s digital business ecosystem and to identify the challenges of legal certainty in ensuring balanced protection for business actors and consumers. The research adopts a normative legal method, employing statutory and conceptual approaches. Primary legal materials include the Law on Electronic Information and Transactions, the Consumer Protection Law, the Trade Law, the Personal Data Protection Law, as well as criminal provisions under the Indonesian Criminal Code and related sectoral regulations. The findings indicate that regulatory transformation has not been adequately accompanied by proportionate and integrated criminal policy formulation, resulting in ambiguity regarding the legal status of digital platforms and uncertainty in the construction of criminal liability. Consequently, a harmonized regulatory model and the reconstruction of criminal provisions grounded in the principles of balanced legal protection, proportional liability, and the doctrine of ultimum remedium are necessary to establish adaptive, equitable, and responsive legal certainty within Indonesia’s digital economy